Comparison of Response to Nitrogen between Upland NERICAs and ITA (Oryza sativa) Rice Varieties - Onaga, Geoffrey; Asea, Godfrey; Lamo, Jimmy; Kikafunda, Joseph; Bigirwa, George (Journal of Agricultural Science, 2012)
Average yields of upland rice are the lowest in Uganda, and most of the productivity gains attributed to improved varieties are related to increased area of production from clearing virgin lands for rice production. In a bid to optimize productivity, we compared the effect of four nitrogen fertilizer treatments: 0, 40, 80 and 120 kgN/ha and two variety types (ITAs (Oryza sativa) and NERICAs (New rice for Africa)) on grain yield and yield parameters in four locations. Combined analysis of variance revealed that nitrogen fertilizer increased mean grain yields from 2116-5200 kg/ha in the NERICAs and 2331-5100 kg/ha in the ITAs. In all the study areas, NERICA 4 and NARIC 2 outperformed NARIC 1 and NERICA 1, and yield trends were consistent over the years suggesting that the two varieties respond better to N fertilizer application. However, the productivity gains are probably related to genetic potential of the varieties rather than the N fertilizer effect, as reflected by the consistent relative performance between 0 N and other N rates. The heavier grains of NARIC 2 and NERICA 4 suggest greater dry matter accumulation before heading, as these varieties have a longer period of vegetative growth. The significant interaction of location x fertilizer and location x variety reveals the need for evaluating the nitrogen-supplying power of soils in the various cropping systems in the country.
Keywords: ITAs; NERICA; Nitrogen fertilizer; Upland rice; Grain yield